Two Styles, One Time: (Literary Form, the Denial of Coevalness, and the Plural East in Doughty’s Travels in Arabia Deserta and Twain’s The Innocents Abroad) - Hussain Waleed Abulfaraj (Journal of Arts, Literature, Humanities and Social Sciences, 2026)
This essay argues that the Orientalism of nineteenth-century travel writing is carried by literary form, and it demonstrates the claim comparatively. The denial of coevalness — the placing of the observed in a time other than the observer’s, in Johannes Fabian’s term — is by now a recognized feature of the genre; this essay asks at what level of the text it is produced. Reading two stylistically antithetical narratives — Charles Doughty’s Travels in Arabia Deserta (1888), written in a deliberately archaic, biblically inflected prose, and Mark Twain’s The Innocents Abroad (1869), written in a brisk American vernacular — it shows that both, by opposite formal means, deny the East a present coeval with the observer’s. Doughty’s scriptural register transposes Arabia into biblical time through diction, syntax, and tense; Twain’s modern, ironic voice fixes the East as belated and unprogressive. That two such different styles converge on the same temporal distancing indicates that the effect is a property of the genre’s forms — the eyewitness posture, the ethnographic present, the spectacle frame — rather than of individual prejudice. Reading with Said, Fabian, Bhabha, Pratt, and Spivak, the essay further argues that the same close attention to style exposes what those forms suppress: an East differentiated by region, tribe, and sect, in which Eastern voices themselves perform acts of distancing. Beneath the single binary the forms inscribe, the texts preserve the outline of a multiply centered Orient — a finding that connects nineteenth-century travel writing to current world-literary debate about centers and peripheries.